Acid-protected Eu(iii) coordination nanoparticles covered with polystyrene. Issue 1 (30th November 2015) - Onodera, Hiromitsu; Kitagawa, Yuichi; Nakanishi, Takayuki; Fushimi, Koji; Hasegawa, Yasuchika
Abstract : Acid-protected Eu(iii ) coordination nanoparticles composed of Eu(iii ) complexes, joint ligands, terminate ligands and a protection layer are reported. Abstract : Acid-protected Eu(iii ) coordination nanoparticles composed of Eu(iii ) complexes, joint ligands, terminate ligands and a protection layer are reported. The prepared acid-protected Eu(iii ) coordination nanoparticles [Eu(hfa)3 (dpbp) x (SDPO) y ] n -PS and Eu(iii ) coordination nanoparticles [Eu(hfa)3 (dpbp) x (SDPO) y ] n were characterized using ESI-mass spectrometry (ESI-MS), X-ray diffraction (XRD), scanning electron microscopy (SEM), dynamic light scattering (DLS) measurements, and thermogravimetric analysis (TGA). [Eu(hfa)3 (dpbp) x (SDPO) y ] n -PS shows an effective acid-resistance property based on the polystyrene layer on its nanoparticle surface. The emission intensity is retained under 3000 s in an acidic condition (pH = 0.92). In this study, acid-protected Eu(iii ) coordination nanoparticles are demonstrated.